Belize : 2021 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Belize. - International Monetary Fund. Western Hemisphere Dept. (Washington, D.C. : International Monetary Fund, 2021)
Belize has been hit hard by the COVID-19 pandemic, which led to a deep recession and worsened fiscal and external positions from already weak levels. The opposition People's United Party won the November 2020 elections by a wide margin, which gives the new government a unique opportunity to jump start much needed reforms to reduce large imbalances and anchor strong and inclusive growth.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements; International Organizations; Monetary Policy; Observance; Belize